Does the Number of Irradiated Cells Influence the Spatial Distribution of Bystander Effects?. Issue 4 (1st October 2014) - Belchior, A.; Balásházy, I.; Gil, O. Monteiro; Vaz, P.; Almeida, P.
There is growing evidence that the radiation effects at low doses are not adequately described by a simple linear extrapolation from high doses, due, among others, to bystander effects. Though several studies have been published on this topic, the explanation of the mechanisms describing the bystander effects remains unclear. This study aims at understanding how the bystander signals are or can be propagated in the cell culture, namely if the number of irradiated cells influences the bystander response. An A549 cell line was exposed to several doses of α-particles, being the bystander response quantified in two non-irradiated areas. The radius of irradiated areas differs by a factor of 2, and the non-irradiated areas were optimally designed to have the same number of cells. Our results show evidence for bystander effects occurring in cells far away from the irradiated ones, meaning that bystander signals can easily spread throughout the cell culture. Additionally, our study highlights that the damage caused by radiation on the surrounding of irradiated areas could be different according to the number of irradiated cells, i.e., for the same dose value; the overall cellular damage could be different.